On the origin of death: Paul and Augustine meet Charles Darwin - Spangenberg, Izak J. J. (HTS teologiese studies, 2013)
Ever since the 4th century, Christian theologians have linked Romans 5:12–21 with Genesis 2–3. Augustine (354–430), one of the Latin fathers of the Church, propagated the idea of ‘original sin’ according to his reading of these chapters. This idea eventually became a fixed doctrine in Western Christianity and a large number of Christians still believe and proclaim that humans would have lived for ever but for the misconduct of Adam and Eve. They also proclaim that Jesus, through his obedience, death and resurrection, re-established God’s original creation plan. Death was conquered and eternal life can be inherited by all who believe in Jesus as saviour and second Adam. However, since both the introduction of the theory of evolution into biology and the paradigm shift in biblical studies (at the end of the 19th century), the view that death was to be linked to ‘original sin’ came under severe criticism. This article argues that Romans 5:12–21 and Genesis 2–3 do not support the idea of ‘original sin’ and that death is a normal part of life on earth, as argued by evolutionary biologists and proclaimed by many Old Testament texts.